Early-Hydration heat and influencing factor analysis of Large-Volume concrete box girder based on equivalent age. (April 2023) - Cai, Yuliang; Wang, Fei; Zhao, Zhuo; Lyu, Zhongda; Wang, Yonggang; Zou, Pan
Abstract: Large-volume concrete box girders are vulnerable to early cracking because of the hydration reaction at early ages. The excessive temperature difference between the core and external surface is the main reason for early cracking. Controlling the temperature field of concrete can reduce the risk of early cracking. Therefore, numerical simulations and tracking tests of a 50-m box girder were conducted. The early-age temperature field was simulated using ABAQUS and the secondary development of the subroutine. Meanwhile, the influences of different construction and curing method parameters were analyzed. The subroutine UMATHT considers the variations of hydration degree, thermal conductivity, and specific heat with equivalent age. The results indicate that the early- age hydration temperature of the box girder follows a general trend of "increasing temperature — continuous high temperature — cooling." The measured results verify the accuracy of the numerical simulation method. The temperature peak and temperature difference between the core and surface increased with the increase in concrete section size, pouring temperature, and cement dosage. The effects of pouring temperature and cement dosage on the temperature rise and cooling rate were reversed. For every 5 °C decrease in the pouring temperature, the temperature peak of the web also decreased by approximately 5 °C, while the temperature difference between the core and surface of the web decreased by approximately 2 °C. When thermal insulation measures were taken for the box girder's outer formwork, the concrete temperature peak increased slightly, but the temperature difference between the core and surface decreased significantly. When the thickness of the polystyrene foam board reached 1 cm, the temperature difference between the core and web surface could be controlled within 6.1 °C.